2000
DOI: 10.1034/j.1399-302x.2000.150513.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of 530‐bp deletion in Actinobacillus actinomycetemcomitans leukotoxin promoter region

Abstract: Actinobacillus actinomycetemcomitans strains showing a 530-bp deletion in the promoter region of the leukotoxin gene operon elaborate high amounts of leukotoxin that may play a role in the pathogenesis of periodontal disease. This study used polymerase chain reaction detection to determine the occurrence of the 530-bp deletion in 94 A. actinomycetemcomitans strains from individuals of various ethnic backgrounds. Eleven blacks and one Hispanic subject but no Caucasian or Asian subjects showed the 530-bp deletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 19 publications
2
47
0
1
Order By: Relevance
“…All highly leukotoxic strains were serotype b, but two serotype b reference strains (ATCC 29524 and Y4) contained the minimally leukotoxic promoter. It has been shown that highly leukotoxic strains of A. actinomycetemcomitans are frequently isolated from LJP patients (12,14), Africans and African-Americans (3,12), and younger subjects (12). In our study, highly leukotoxic strains comprised 25% of the isolates from LJP patients (5 of 20) and 25% of the isolates from healthy subjects (1 of 4).…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…All highly leukotoxic strains were serotype b, but two serotype b reference strains (ATCC 29524 and Y4) contained the minimally leukotoxic promoter. It has been shown that highly leukotoxic strains of A. actinomycetemcomitans are frequently isolated from LJP patients (12,14), Africans and African-Americans (3,12), and younger subjects (12). In our study, highly leukotoxic strains comprised 25% of the isolates from LJP patients (5 of 20) and 25% of the isolates from healthy subjects (1 of 4).…”
Section: Resultsmentioning
confidence: 77%
“…Highly leukotoxic strains also comprise approximately one-half of the strains isolated from Africans and African-Americans but only 0 to 2% of strains isolated from Europeans and Asians (3,12,14,15). These findings led to the hypothesis that LJP may have two different etiologies and epidemiologies: in Caucasians LJP may be associated with diverse A. actinomycetemcomitans clones acting as opportunistic pathogens, whereas in some Africans and African-Americans LJP may be associated with JP2-like strains acting as exogenous pathogens (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microorganisms produce several virulence factors that could be involved in the destruction of periodontal tissues. The most important one seems to be leukotoxic activity (46,47) . The highly leukotoxic bacterial strains of Aa (strain JP2) can produce 10 to 20 times more toxins than other strains, giving them the potential to interfere with innate immune host defenses (48) .…”
Section: Microbiologymentioning
confidence: 99%
“…Members of a particular clonal lineage (JP2) of A. actinomycetemcomitans (18) show a unique 530-bp deletion (⌬530) in the promoter region of the ltx operon resulting in enhanced production of leukotoxin, a key virulence factor (1). The JP2 clone shows marked racial tropism as it has been isolated almost exclusively from adolescent periodontitis patients of West and Northwest African descent, including both Africans and Arabs (2,3,4,5,6). Substantial evidence shows that the JP2 clone induces aggressive periodontitis in these populations and constitutes a particularly pathogenic subpopulation of A. actinomycetemcomitans (see reference 6a); reviewed in reference 8).…”
mentioning
confidence: 99%